Health-relevant pollutants in US landscape fire smoke: abundance, health impacts, and influence on indoor and outdoor air quality - O'Dell, Katelyn, author; Pierce, Jeffrey R., advisor; Fischer, Emily V., advisor; Collett, Jeffrey L., Jr., committee member; Ford, Bonne, committee member; Magzamen, Sheryl, committee member (Colorado State University. Libraries, 2021)
Landscape (wild, prescribed, and agricultural) fires have a significant impact on air quality in the United States (US). As anthropogenic emissions decline and emissions from landscape fires increase across the coming century, the relative importance of landscape fire smoke on US air quality and health will increase. Landscape fire smoke is a complex mixture of multiple gas- and particle-phase pollutants, which are harmful to human health. The health impacts of landscape fire smoke may differ from urban pollution as the seasonal and spatial distribution, particle size distribution and composition, and relative abundance of gas-phase species in landscape fire smoke are different from urban pollution sources. Epidemiology studies of smoke events, which often rely on particulate matter (PM) concentrations as a smoke exposure tracer, show smoke negatively impacts respiratory health. The contribution of gas-phase hazardous air pollutants (HAPs) to the health impacts of smoke has yet to be directly quantified. In addition, the implications of episodic landscape fire emissions on the sub-national temporal and spatial distribution of health events are not well characterized. Finally, a majority of the work on the health and air quality impacts of landscape fire smoke has focused on outdoor air. Recent works have shown that landscape fire smoke can impact indoor air quality, but there is large heterogeneity in both smoke events and the indoor environments impacted by smoke events. To date, no study of US wildfire smoke influence on indoor air quality has analyzed indoor fine particulate matter (PM2.5) concentrations across multiple western US cities during multiple extreme smoke events. In the first chapter of this dissertation, we combine aircraft-based in-situ smoke plume observations with interpolated regulatory surface monitor observations to quantify the health risk of HAPs in US smoke. Using observations from the Western Wildfire Experiment for Cloud Chemistry, Aerosol Absorption, and Nitrogen (WE-CAN), a 2018 aircraft-based field campaign that measured HAPs and PM in western US wildfire smoke plumes, we identify the relationships be- tween HAPs and associated health risks, PM, and smoke age. We find the ratios between acute, chronic noncancer, and chronic cancer HAPs health risk and PM in smoke decrease as a function of smoke age by up to 72% from fresh (<1 day of aging) to old (>3 days of aging) smoke. We show that acrolein, formaldehyde, benzene, and hydrogen cyanide are the dominant contributors to gas-phase HAPs risk in smoke plumes. We use ratios of HAPs to PM along with annual average smoke-specific PM to estimate current and potential future smoke HAPs risks. Next, we use a health impact assessment with observation-based smoke PM2.5 to determine the sub-national distribution of mortality and the sub-national and sub-annual distribution of morbidity attributable to US smoke PM2.5 from 2006-2018. We estimate disability-adjusted life years (DALYs) for PM2.5 and 18 gas-phase HAPs in smoke using the HAPs to PM ratios developed in Chapter 2. Although the majority of large landscape fires occur in the western US, we find the majority of mortality (74%) and morbidity (on average 75% across 2006-2018) attributable to smoke PM2.5 occurs outside the West due to a higher population density in the East. Across the US, smoke-attributable morbidity predominantly occurs in spring and summer. The number of DALYs associated with smoke PM2.5 are approximately three orders of magnitude higher than DALYs associated with gas-phase smoke HAPs. These results indicate that awareness and mitigation of landscape fire smoke exposure is important across the US, not just in regions in proximity to large wildfires. Finally, we use a large low-cost sensor network of indoor and outdoor PM2.5 monitors to characterize the relationship between indoor and outdoor air quality during smoke events. We identify smoke-impacted regions of the western US with a high density of co-located (distance < 1000 m) indoor and outdoor PurpleAir monitors. In these regions, we calculate indoor PM2.5/outdoor PM2.5 ratios on smoke-impacted and smoke-free days and find this ratio is < 1 (indoor PM2.5 less than outdoor PM2.5) at 98% of the monitor pairs for smoke-impacted days, compared to 54% on smoke- free days. On smoke-impacted days, indoor PM2.5 concentrations increase as outdoor PM2.5 Air Quality Index (AQI) increases by 25% per AQI bin, on average. However, the ratio of indoor PM2.5 to outdoor PM2.5 decreases by 28% per AQI bin. These results show that landscape fire smoke influences indoor air quality across many indoor environments in multiple cities, and this impact increases with smoke event intensity. In addition, this work highlights the utility of low-cost monitoring in quantifying indoor air quality during smoke events. However, we show that the present distribution of these indoor monitors suggests a bias towards census tracts of lower social vulnerability.
Keywords: biomass burning; health; wildfire; hazardous air pollutants; air quality; particulate matter